2013
DOI: 10.1080/13607863.2013.856857
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with anger and anger expression in caregivers of elderly relatives

Abstract: Results highlight that interventions aimed to improve caregivers' strategies to address memory and behavior problems and to promote the use of effective coping strategies could be helpful to prevent anger and expression-out of anger. Reducing burden in caregivers might result in reductions of anger expression-in. Data underscore the need to consider anger feeling and both in-expression and out-expression of anger separately in order to understand anger experience in caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Self-efficacy for controlling upsetting thoughts has also been found to partially mediate the relationship between caregiving burden and depression in a longitudinal sample (Grano et al, 2017). This specific construct has proved important to caregiver mental health crossnationally, such as in the United States, Canada, Italy, Spain, and China (Crespo and Fernández-Lansac, 2014;Grano et al, 2017;Marziali and Garcia, 2011;Steffen et al, 2018;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…Self-efficacy for controlling upsetting thoughts has also been found to partially mediate the relationship between caregiving burden and depression in a longitudinal sample (Grano et al, 2017). This specific construct has proved important to caregiver mental health crossnationally, such as in the United States, Canada, Italy, Spain, and China (Crespo and Fernández-Lansac, 2014;Grano et al, 2017;Marziali and Garcia, 2011;Steffen et al, 2018;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…Because the role of coping has been extensively evaluated in studies of caregivers (Crespo & Ferná ndez-Lansac, 2013;Haley, Levine, Brown, & Bartolucci, 1987;Ló pez et al, 2005;Noonan & Tennstedt, 1997), we focused this investigation on the other mediator considered in the caregiver stress model (Pearlin et al, 1990), that is, the social support of caregivers. In particular, we asked through a series of YES/NO questions about the different types of support the caregivers used, such as the help provided by the general practitioner, dementia supervisor, relatives and friends, home services, respite care services, and self-help groups.…”
Section: Mediatorsmentioning
confidence: 99%
“…The likely outcomes of the SPM of Pearlin et al (1990) involve the well-being of the caregiver and their physical and mental health. The majority of research regarding caregivers of patients with dementia has employed the model linked to negative aspects of caregiving (Crespo & Ferná ndez-Lansac, 2013). Therefore, our model incorporates a modification to the model of Pearlin et al with the treatment of what they considered to be personal gain as a positive outcome represented by caregiving satisfaction (see Fig.…”
Section: Introductionmentioning
confidence: 98%
“…higher burden, 11 distress, 12,13 and anger. 14,15 As we argued that higher caregiving demands might be associated with perceptions of injustice, and studies among other groups (e.g. patients with pain) have shown that perceived injustice is associated with more negative psychological outcomes, such as higher depression, anxiety, and anger, 2,5,16,17 it seems logical to consider perceived injustice as a mediator in the link between caregiving demands and family caregivers' psychological well-being.…”
Section: Introductionmentioning
confidence: 96%